Optimization Ultrasonic Assisted Extraction of Dye from African Tulip Leaves (Spathodea Campanulata P. Beauv) and Optimization of it’s Application as A Textiles Dye - Silvia Tri Ayu Ningtias; Harjono Harjono; Cepi Kurniawan; Samuel Budi Wardhana Kusuma (Indonesian Journal of Chemical Science, 2023)
Along with the development of the textile industry in Indonesia, the use of synthetic dyes is also increasing. The use of natural dyes is an alternative to synthetic dyes because they are not toxic and harmless to the environment. African tulip leaves (Spathodea Campanulata P. Beauv) have potential as natural dyes because they contain tannins and flavonoids. African tulip leaf dyes were obtained by Ultrasound-assisted Extraction (UAE) extraction with variations in extraction times of 15, 30, 45 and 60 minutes with the solvents used, namely ethanol and methanol. This research was conducted with the aim of knowing the effect of the type of solvent and extraction time on the dye content and test the resistance of the dye extract to washing. The results showed that the most optimal time for extraction of UAE in ethanol solvent was 15 minutes and methanol was 30 minutes. The process of applying the dye used the mordant KAl(SO4)2 and FeSO4 with various concentrations (0, 10, 20, 30 g/L) to increase the fastness to washing. The best results were shown by cotton cloth with the KAl(SO4)2 mordant at a concentration of 30 g/L, while the FeSO4 mordant at a concentration of 10 g/L was proven by a low ∆E value. The characterization results of African tulip leaf extract using FTIR and UV-Vis spectrophotometer showed the presence of flavonoids and tannins in the extract characterized by the presence of functional groups O-H, C-H, C=C, C=O, C-O-C, and C-O and the presence of peaks in the flavonoid absorption area and the visible light region at a wavelength of 662 and 660 nm.